Images of Care: Marriage, Family Making, and the Reproduction of the Social Order in Tajikistan - Elena Borisova; Swetlana Torno (Journal of Eurasian Studies)
Marriage is a central event in all Central Asian societies and is particularly important for the lives of individuals, kinship groups, and society more broadly. Within the regional scholarship, it serves as an entry point for the study of a wide range of topics and the exploration of social, political, economic, and religious dynamics. This article aims to shift the perspective on Central Asian marriages from questions of political economy and identity to the circulation of care by scrutinising its role in social reproduction across the scales of the individual body, family, community, and the state. Drawing on the ethnographic material collected by the authors during extensive fieldwork in two localities in Tajikistan, this article analyzes care practices in several domains: organising the daughter’s dowry, assembling the bride’s fashions, preparing food and serving the guests, maintaining family’s reputation and status, caring for the reproduction of tradition, and the state’s care for families. We argue that feminist and anthropological studies that draw attention to care’s productive as well as disruptive sides are helpful for understanding how these practices contribute to reproducing old and forging new types of relatedness and maintaining complex social worlds. Working with care practices visually, alongside textual representations, allows us to convey people’s enormous affective, material, and labour investments in marriages and to draw attention to the visible and invisible aspects of these practices.